Detection of some virulence factors of Pseudomonas aeruginosa isolated from wound infections and the effect of some antibiotics on them (Journal of the College of Basic Education, 2022)
A total of 126 samples of clinical injuries were collected from various hospitals in the Iraqi capital Baghdad. For the diagnosis of P.aeruginosa isolates, the isolates were cultured on agricultural media, MacConkey agar and solid cetrimide agar. Biochemical tests were carried out ant it was appeared that 25 isolates were P.aeruginosa, which represent 19.48% of total number of isolates. Four bacterial isolates showed a capability of producing lipase enzyme 16%, while all isolates were unable to produce urease, whereas all bacterial isolates showed the ability to degrade gelatinase 100%, and 16 isolates were able to produce Protease 64%.In the process of detecting the susceptibility of bacterial isolates to the production of Siderophore, it was found that all isolates are capable of producing it 100%. Concerning the capability of producing Hemolysin, it appeared that only 24% of isolates produced it when grown on solid blood medium, the rest of the isolates were unable to produce it. All the bacterial isolates that had been studied showed ability for the Twitching motility and Swimming Motility that means a rate of 100%, while 24 isolates except one isolate only from total number of isolates were uncapable of Bacterial Swarming 96%. The isolates sensitivity of 6 antibiotics was tested using Disk Diffusion Method. The results showed that all bacterial isolates were resistant to Ceftazidime 100%, whereas only 11 isolates were resistant to antibiotics Ciprofloxacin 44%,13 isolates showed resistance to each type of the antibiotics Tobramycin and Gentamicin that equals a rate of 52%, while no bacterial isolates had been able to resist The antibiotic Imipenem, and for the antibioticGentamicinonly5bacterial isolates were able to resist it 20%.